PENGARUH JOB ENRICHMENT, MOTIVASI KERJA, DAN PEMBERIAN INSENTIF TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. FAJAR SURYA WISESA. TBK - Gilang Wahyu Armanda; Lukman Hakim (Jurnal Bina Bangsa Ekonomika, 2024)
The purpose of this study is to analyze  the effect of job enrichment, work motivation, and providing incentives on employee job satisfaction at PT. Dawn Surya Wisesa. This research method is quantitative. The population of this study is all employees or workforce at PT. Fajar Surya Wisesa Tbk who has been working at the company for more than one year. The sample size of this study was 125 respondents. The type of data used in this study is primary data. The sampling technique in this study used probability sampling design. Data analysis techniques used to analyze the influence of independent variables on dependent variables, where testing stages are needed through statistical analysis with the help of SPSS applications. The result of this study is that there is no significant effect  of job enrichment variables  on job satisfaction of PT employees. PT. Fajar Surya Wisesa Tbk. There is a significant influence of work motivation on job satisfaction of PT. PT. Fajar Surya Wisesa Tbk. There is a significant influence of variable incentive on employee job satisfaction of PT. PT. Fajar Surya Wisesa Tbk